(untitled) (International Journal of Nursing Education, 2021)
Background: Suboptimal academic performance by the majority of students at higher educational level has been linked with ineffective teaching methods by teachers/lecturers.The aim of this study was to assess teaching methods, academic, and clinical performances among student nurses in schools of nursing, in North-west Nigeria. .Methods: The study adopted a mixed approach of a cross-sectional design.The sample comprises of 95 tutors, 31 clinical instructors, 698 students, and the final year students from five selected schools. An adapted questionnaire was used for data collection. Quantitative data were analyzed using descriptive and inferential statistic with the aid of IBM SPSS Version 20. The qualitative data were summarize using thematic content analysis. Results: Lectures, demonstration, and discussion were the most frequently used methods of instruction in the schools. The average academic performances of students were credit (C). The academic performance of students in the final examination and Nursing Council Exam was “Pass”. Most of the students obtained a C-grade in the clinical examination. The clinical performance rating of the students in both the school and the nursing Council was “Pass” grade. There was a Significant positive correlation between the academic performance of third year students and their clinical performance (<.05). Most students were satisfied with lecture teaching method because of its ability to ensure curriculum coverage. Conclusions: Clinical performance of students increased with an increased academic performance. Students preferred lectures and demonstration as methods of instruction. The tutors should trained and motivated students to use students’ centred Learning methods in the administration of their lessons.